The Specific Features of The Use of Numerical Components In Idioms and Proverbs - Nematjanova, Dilafruz (Indonesian Journal Publisher, 2025)
This research explores the cultural and symbolic significance of numerical components in Uzbek idioms and proverbs. The study aims to identify the meanings and roles of key numbers such as three, seven, and forty in traditional ceremonies, social customs, and linguistic expressions. Using a qualitative descriptive methodology, data were collected from linguistic sources, ethnographic studies, and cultural references. The results indicate that numbers serve as metaphors for societal values, historical transitions, and ritual practices, reinforcing their importance in Uzbek linguistic and cultural identity.